3D seismic simulation analysis of the Longtoushan Town Basin during the 2014 Ludian earthquake, Yunnan province - Li, Chengcheng; Liu, Peng; Liu, Zhongxian; Yuan, Xiaoming; Tian, Yuan; Zhang, Hai; Cao, Zhenzhong (Frontiers in Earth Science, 2023)
On August 3, 2014, a magnitude Ms 6.5 earthquake struck Ludian County, Zhaotong City, Yunnan Province, causing grave losses of life and property in the Longtoushan Town Basin near the fault. In this study, a three-dimensional model of the Longtoushan Town Basin and the velocity structure of the surrounding area, and the Spectral Elements in Elastic Dynamics code, which combines the discontinuous Galerkin technique and the spectral element method (SEM) are used to simulate and study the entire seismic wave propagation process. The results show that due to the variations in the basin geometry and the impedance ratio of the media inside and outside the basin, the seismic waves incident on the basin edge are refracted and diffracted, further prolonging the ground motion holding time within the basin. In the bedrock outside the basin, the velocity peaks are higher at higher elevations; viceversa within the basin, the locally depressed basement produces an obvious amplification effect. The amplitude of the ground motion is not the greatest in the thickest sedimentary layers in the basin, and it is closely related to the degree of undulation at the base of the sedimentary layers, the overburden thickness, and the basin geometry. The peak ground accelerations (PGAs) of approximately 8 m/s2 in the east–west (E–W) direction and 3 m/s2 in the north–south (N–S) direction are influenced by the rupture directivity effect (the ruptured surface is the Baogunao–Xiaohe fault that is oriented in the N–W direction). The peak ground velocity with a sedimentary model is 2.6 and 1.6 times that of the non-sedimentary model in the E–W and N–S directions, respectively. The maximum amplification factor for PGA in the E–W direction is 2.8 and that in the N–S direction is approximately 2.3. The results are in agreement with the actual observed seismic station data in terms of the waveforms and peaks, and the intensity distribution map matches the actual damage distribution. This proves the accuracy and rationality of the method used in this study. The results are useful for the seismic zoning of cities, and they can help engineers predict ground motions for future large earthquakes.